1998
DOI: 10.1076/ceyr.17.5.501.5194
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelet-activating factor in cell infiltration in endotoxin-induced uveitis in guinea pigs

Abstract: These results suggest that PAF has weak direct activity on cell infiltration in intraocular inflammation but enhances intraocular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In a previous report, when LPS was injected intracamerally, PAF was detected in the aqueous humor and found to enhance the intraocular inflammation (35). In this study, we found that LPS induces the mRNA expression of the PAF receptor in ARPE19 cells.…”
Section: Discussionsupporting
confidence: 67%
“…In a previous report, when LPS was injected intracamerally, PAF was detected in the aqueous humor and found to enhance the intraocular inflammation (35). In this study, we found that LPS induces the mRNA expression of the PAF receptor in ARPE19 cells.…”
Section: Discussionsupporting
confidence: 67%